The "New" EMS - Francesco Giavazzi; Luigi Spaventa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1990)
In the past three years, the countries that belong to the Exchange Rate Mechanism of the European Monetary System (EMS) have experienced a very rapid process of financial integration.
Keywords: 330